Gross Hematuria, a rare manifestation of placenta percreta: a case report - Marzieh Lotfalizadeh; Seyedeh Azam Pourhoseini; Salmeh Dadgar; Somayeh Moein Darbari; Seyed Hamed Ghadamgahi; Asieh Maleki (Mashhad University of Medical Sciences, 2021)
Introduction: Abnormal placental implantation with bladder invasion is a rare obstetric complication, which can be accompanied with severe maternal and fetal morbidity. Gross hematuria is a rare manifestation of these syndromes, placenta percreta. Awareness of rare and unusual manifestations of placenta accrete syndromes is crucial for effective and timely management of this condition. In this report, a case of placenta percreta with manifestation of gross hematuria is introduced. Case presentation: The patient was a 32-year-old pregnant woman at 17 weeks of gestation and a history of two previous cesarean sections who was evaluated with MRI following gross hematuria and suspicion of abnormal placental adhesion. Hysterectomy was performed with the diagnosis of placenta percreta and due to severity of placental invasion.  Conclusion: In the evaluation of a pregnant woman with gross hematuria, even as very early, especially with history of previous cesarean sections, awareness of probable diagnosis of placenta percreta with urinary tract involvement is needed for timely diagnosis and proper management.